Peran Kepramukaan dalam Meningkatkan Kemandirian Remaja - Siti Saharia; Diva Israyati; Febronia Suwanti; Numrotul Inayah; Abuzar Algifari; Mario Keviandro Emanuel Wetter (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
This research is entitled The Role of Scouting in Increasing Adolescent Independence. Scouting is a movement that provides attitudes and skills to students, including teenagers. This research aims to describe the role of Scouts in supporting adolescent independence. The method used is a qualitative method with literature study. The research results show that these benefits are (1) helping participants to make their own decisions, (2) helping participants to work independently, (3) helping participants to face challenges, (4) helping participants to develop self-confidence, (5) help participants to develop the ability to work together in teams. Apart from that, pioneering activities can also help participants to develop good characters, such as: Perseverance, Tenacity, Accuracy, Creativity.